Gender and the pursuit of small prey: archaeological, historical and iconographic perspectives on trapping, falconry and ferreting - Fowler, Thomas A. (2016)
The remains of small animals are seldom recovered in great numbers during archaeological excavation. These taxa are therefore often neglected by zooarchaeologists because species recovered in great quantities are assumed to be the most ‘important’. Zooarchaeological narratives on human interactions with wild fauna are therefore constructed with a bias towards big game hunting and therefore towards adult, most often elite, men whilst other social groups, such as women and children are ignored. This study assesses the potential for research on small wild animals to contribute to human-animal studies, to inform us about the construction of gender identity and to address androcentrism in archaeological research.